(untitled) (Journal of the College of Basic Education, 2026)
The current research aims to identify: The effectiveness of the cartoon strategy in developing environmental awareness among first-year middle school students. To identify the percentage of gain achieved by the independent variable (cartoon strategy) on the dependent variable (environmental awareness(. To achieve the research objectives، the researcher adopted the experimental approach in constructing his research procedures. He adopted the Environmental Awareness Scale prepared by (Ibrahim، 2021) after verifying its psychometric properties. The results indicated that the values ​​of the validity and reliability coefficients were high and statistically significant for the validity of the scale. The researcher also prepared a teacher’s guide for using the proposed cartoons to teach basic concepts of environmental awareness. The research was applied to two samples: the first was a statistical sample consisting of (300) male and female students from first-year middle school; To apply the environmental awareness scale adopted by the researcher، and the second is an experimental sample consisting of (64) male and female students، (32) male students from Al-Falah Intermediate School for Boys and (32) female students from Umm Amara Intermediate School for Girls. To reach the results، the researcher used the statistical package (SPSS)، and the results showed the effectiveness of the cartoon strategy in developing environmental awareness among students in the experimental group. In light of the results and conclusions that resulted from the research، the researcher recommended and proposed a set of recommendations and proposals.